Endosalpingiosis of the Gallbladder: A Unique Complication of Ruptured Ectopic Pregnancy - Porter, Katherine R (Cureus, 2019)
A 60-year-old woman with a history of a ruptured ectopic pregnancy and subsequent salpingo-oophorectomy presented with clinical signs. Pre-operative imaging and intra-operative observations were highly suggestive of acute on chronic cholecystitis. A laparoscopic cholecystectomy was performed. In addition to confirming calculous cholecystitis, final pathology revealed endosalpingiosis on the serosal surface of the gallbladder. Endosalpingiosis is a rare, benign presence of glands lined by tubal-like epithelium, and the few case reports describe it on the surface of the female reproductive organs or seeded on the pelvic peritoneum. We hypothesize that, in this unique case, the endosalpingiosis is due to patient’s ruptured ectopic pregnancy, which allowed tubal epithelial cells to spread to the gallbladder. The only documented cases of endosalpingiosis outside the pelvic and lower abdominal organs have been congenital choristomas. To our knowledge, this is the first documented case of acquired endosalpingiosis of the gallbladder.